GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 3283 species occurrences available in GBIF matching the query: TaxonKey: Centaurea scabiosa Asso HasGeospatialIssue: false HasCoordinate: true Year: >= 2010. The dataset includes 3283 records from 50 constituent datasets: 514 records from naturgucker. 1 records from EDIT - ATBI in Gemer area (Slovakia). 4 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 2 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 8 records from Dutch Vegetation Database (LVD). 3 records from Vascular Plants, Observations, Oslo (O). 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 7 records from Online Atlas of vascular plants 2012-2020. 1 records from Ireland's BioBlitz 2012. 355 records from BioFokus. 1 records from Staffordshire Ecological Record - SER Site-based Surveys. 6 records from SWECO. 7 records from University of Vienna, Institute for Botany - Herbarium WU. 802 records from Artdata. 12 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 27 records from ArtenFinder. 9 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 2 records from Vascular Plant Herbarium, Oslo (O). 306 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 65 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Fieldjournal.org observation database. 1 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 2 records from Natural History Museum, Vienna - Herbarium W. 2 records from Jordal. 22 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 6 records from Herbarium Berolinense. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 4 records from The Flora of County Wexford. 9 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 105 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 8 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 293 records from Observations du Conservatoire botanique national du Bassin parisien.. 99 records from Carnet en Ligne. 1 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 2 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 324 records from Norwegian Species Observation Service. 13 records from Tiroler Landesmuseum Ferdinandeum. 4 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 29 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 1 records from Anymals+plants - Citizen Science Data. 2 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 175 records from Biological and palaeontological collection and observation data MNHNL. 4 records from Estonian Nature Observations Database. 27 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 2 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 8 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia.
Keywords: GBIF; biodiversity; species occurrences